2015
DOI: 10.1111/tbed.12429
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of Antibodies Against African Swine Fever Virus in Faeces Samples

Abstract: African swine fever (ASF) is a viral, highly lethal haemorrhagic disease of swine with no available vaccine or effective treatment. Introduction of ASF into a country triggers immediate restriction measures that cause significant economic losses and threatens spread to neighbouring countries. Wild boar populations have been recently assigned an essential role in the spread of African swine fever virus (ASFV) to European countries. Therefore, effective surveillance and monitoring of wild boar populations is req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…[ 39 ] reported that the enzymatic lysis method is the preferred method to extract bacterial DNA in stool samples, several commercial DNA extraction kits appear adequate [ 39 ]. We choose the Saliva DNA Isolation Kit (NORGEN BIOTEK CORPORATION), which has been used for many studies [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 39 ] reported that the enzymatic lysis method is the preferred method to extract bacterial DNA in stool samples, several commercial DNA extraction kits appear adequate [ 39 ]. We choose the Saliva DNA Isolation Kit (NORGEN BIOTEK CORPORATION), which has been used for many studies [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that pigs that survive natural infection usually develop antibodies against ASFV from 7 to 10 days post-infection which persist for a long period of time [ 45 ]. Therefore, the detection of specific antibodies against ASFV is very useful for the diagnosis of inapparent forms of ASF [ 46 ]. Thus, despite the short duration of the experiment, this animal would represent an ASF subclinical case.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, non‐invasive sampling methods are lacking, which are especially important for ASF control in northern Europe. Samples obtained through non‐invasive sampling methods such as oral fluid and faeces allow ASFV and anti‐ASFV antibodies detection (Davies et al., ; De Carvalho Ferreira, Weesendorp, Quak, Stegeman, & Loeffen, ; Giménez‐Lirola et al., ; Mur et al., ; Nieto‐Pelegrín, Rivera‐Arroyo, & Sánchez‐Vizcaíno, ). Commercial tests based on oral fluid are already available for porcine reproductive and respiratory syndrome as well as sampling guidelines for oral fluid‐based survey on grouped‐housed animals (Rotolo et al., ).…”
Section: Asf Diagnosis and Potential Vaccinesmentioning
confidence: 99%